Q:

Which equation shows an example of the associative property of addition? (–7 + i) + 7i = –7 + (i + 7i) (–7 + i) + 7i = 7i + (–7i + i) 7i × (–7i + i) = (7i – 7i) + (7i × i) (–7i + i) + 0 = (–7i + i)

Accepted Solution

A:
The correct answer is the first option, which is:

 (–7 + i) + 7i = –7 + (i + 7i)

 The explanation is shown below:

 1. By definition, in the associate property of addition you summ the number by grouping them with parenthesis, without matter where you use those parenthesis.

 2. Therefore, as you can see, you can obtain the result of the addition  by agruping the numbers (–7 + i) + 7i or  –7 + (i + 7i) .